Lembar Kerja Siswa (LKS) Berbentuk Komik Berorientasi Problem Solving Untuk Mengembangkan Karakter Peduli Lingkungan - Atikah, Atikah; Yulianti, Dwi; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2020)
This study aims to describe the science worksheets design in comic form with problem solving oriented to develop students care environment character, determine the validity of the worksheets, the readability of the worksheets, and students care environment character development. The results showed that the design of this student worksheet was in comic form with problem solving oriented, the validity level of the student worksheet obtained proper criteria and had a high readability level so that it was easy to understand. The use of student worksheets in learning can improve student learning outcomes in the cognitive domain and develop an environment care character